Factors Influencing Co-Worker Support Among Employees at The Workplace : A Systematic Literature Review - Andre Nugraha Wijaya; Fatwa Aji Wiguna; Unika Prihatsanti (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Co-worker support is a crucial factor in creating a positive and productive work environment. This study aims to summarize recent findings from various studies on factors that influence the level of coworker support in the workplace. Through a comprehensive literature review, this study identifies a number of variables that are consistently associated with co-worker support, such as organizational climate leadership, employee personality, and job characteristics. This study used PRISMA as a research method with the article search included databases from Scopus, Science Direct, and Emerald Insight with the keyword “co-worker support” AND “among Employees” AND “work-place”. Based on the inclusion criteria, eight articles were obtained for further analysis, From the eight articles studied, it was concluded that the factors that influence co-worker support are divided into internal and external factors. The results of this literature review are expected to provide a deeper understanding of the factors that organizations need to pay attention to in an effort to increase co-worker support. The findings of this review can also form the basis for further empirical research to test the generalizability of previous findings and develop effective interventions to increase co-worker support across organizational contexts.